2018
DOI: 10.1093/ijnp/pyy054
|View full text |Cite
|
Sign up to set email alerts
|

Functional Connectivity of the Raphe Nuclei: Link to Tobacco Withdrawal in Smokers

Abstract: BackgroundAlthough nicotine alters serotonergic neurochemistry, clinical trials of serotonergic medications for smoking cessation have provided mixed results. Understanding the role of serotonergic dysfunction in tobacco use disorder may advance development of novel pharmacotherapies.MethodsFunctional magnetic resonance imaging was used to measure resting-state functional connectivity of the raphe nuclei as an indicator of serotonergic function. Connectivity of the dorsal and median raphe nuclei was compared b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

5
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…At the beginning of the testing session, participants underwent MRI scanning while in the resting state. These procedures were part of a larger testing battery (data reported in Faulkner et al, 2018a and to be reported elsewhere). For smokers, the average duration of abstinence from smoking prior to the resting state fMRI scan was 49.87 minutes (SD = 41.22 minutes).…”
Section: Methodsmentioning
confidence: 99%
“…At the beginning of the testing session, participants underwent MRI scanning while in the resting state. These procedures were part of a larger testing battery (data reported in Faulkner et al, 2018a and to be reported elsewhere). For smokers, the average duration of abstinence from smoking prior to the resting state fMRI scan was 49.87 minutes (SD = 41.22 minutes).…”
Section: Methodsmentioning
confidence: 99%
“…Exclusion criteria for both studies were self‐report of psychiatric comorbidity; current drug use/abuse or dependence (other than tobacco use disorder or cannabis use); history of neurological injury or disease, pregnancy, and contraindications for MRI (e.g., metal implants). Twenty participants were defined as daily smokers because they smoked at least five cigarettes every day for at least 1 year, in line with definitions in previous research 5,6,8,24–27 ; 24 participants were defined as intermittent smokers because they smoked between one and four cigarettes on at least 1 day per week; 41 participants were defined as nonsmokers because they smoked 0 cigarettes per day. Data from study 1 were collected from November 2015 to March 2018, whereas presented data from study 2 were collected from September 2017 to August 2019.…”
Section: Methodsmentioning
confidence: 96%
“…Exposure to cigarettes was inferred from the average number of cigarettes smoked per day as in previous research (e.g. Durazzo et al, 2016; Faulkner et al, 2018; 2019; 2020b). Participants also completed the Depression, Anxiety and Stress Scale (DASS), a 42-item questionnaire designed to quantify levels of depression, anxiety and stress; each of these emotional symptoms is assessed by summing the answers to fourteen 4-point Likert scale questions (Lovibond and Lovibond, 1995).…”
Section: Methodsmentioning
confidence: 99%